2018
DOI: 10.1590/1981-22562018021.170204
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among participants of an Open University of the Third Age and associated factors

Abstract: Objective: to identify the prevalence of self-medication, the therapeutic classes used without medical prescription, the symptoms treated with such medication and associated factors among participants of an Open University of the Third Age (OU3A). Method: a cross-sectional, descriptive and analytical study was carried out, the sample of which was composed of 138 OU3A attendees. To estimate the association between the variables, prevalence ratios (PR), confidence intervals (95% CI), the chi-squared test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…Studies have identified a relatively high prevalence of self-medication practice in several countries, including Brazil [5][6][7][8][9][10][11]. Factors contributing to this high prevalence include the wide variety of over-the-counter drugs and advertising campaigns that use the strategy of overemphasizing benefits and hiding the risks of medicines [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have identified a relatively high prevalence of self-medication practice in several countries, including Brazil [5][6][7][8][9][10][11]. Factors contributing to this high prevalence include the wide variety of over-the-counter drugs and advertising campaigns that use the strategy of overemphasizing benefits and hiding the risks of medicines [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Em suma, a prática da automedicação expõe, principalmente os idosos, a eventos adversos e riscos iatrogênicos que podem prejudicar sua autonomia e capacidade de participação. (SANTOS et al, 2018;.…”
Section: Discussionunclassified
“…Entre 2009 e 2015, em oficinas de orientação sobre o uso de medicamentos oferecidas junto à UATI/EACH, observou-se que os idosos que a frequentam são, em sua grande maioria, indivíduos autônomos e socialmente ativos com acesso a serviços de saúde e consumidores de medicamentos, sobretudo os de uso contínuo (Santos et al, 2018), em geral para tratar suas doenças crônicas. Em estudo realizado com 121 idosos da UATI/EACH/USP, observou-se que mais de 80% possuía pelo menos uma doença cardiometabólica, sendo a hipertensão a mais prevalente e mais de 90% consumia medicamentos prescritos de uso contínuo.…”
Section: Relato De Experiência Na Pesquisa E Ensino Na Universidade A...unclassified